The Effectiveness of Elementary Teacher Digital Literacy Competence on Teacher Learning Management - Marnita Marnita; Diding Nurdin; Eka Prihatin (Yayasan Keluarga Guru Mandiri, 2023)
An educator or teacher must have adequate ability to use digital technology and communication tools to access, use, and even evaluate digital-based learning processes. This ability is referred to as the digital competence of a teacher in training his students to build new knowledge actively and creatively, which is very closely related to the lives of Generation Z who are active students today. The purpose of this study is to analyze the Digital Literacy Competence of Elementary School Teachers on Teacher Learning Management in Gandapura District. The sample in this study were elementary school teachers with thematic learning. The technique of data analysis through data reduction is by selecting every incoming data through observation, interviews, and documentation which are then summarized and selected according to the indicators needed. The findings of this study are that public elementary schools in Gandapura District have teachers who understand digitalization with low, medium, and high levels of understanding. So, it can be concluded that the digital competence of teachers has a good contribution to the development of effective and efficient teacher learning management. Teachers' digital literacy competencies can create student enthusiasm and harmony between teachers and students in the class on thematic lessons, especially science which is usually more difficult for students.